2003
DOI: 10.1002/eji.200324034
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor T cell response and protective immunity in mice that received sublethal irradiation and immune reconstitution

Abstract: To test whether homeostasis-driven T cell proliferation in reconstituted lymphodepleted hosts would improve the therapeutic efficacy of tumor vaccines, normal mice and reconstituted lymphopenic mice (RLM; C57BL/6 mice rendered lymphopenic with sublethal totalbody irradiation and reconstituted with naive splenocytes) were used in the vaccination and challenge experiments with weakly immunogenic F10 melanoma cells. Only limited protection was observed in vaccinated normal mice (16.7%), whereas significantly grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 39 publications
0
61
0
Order By: Relevance
“…[8][9][10]27,28 In particular, a number of studies have investigated the combination of CTX with various vaccines. [4][5][6][7]29,30 However, in most of those studies a low dose of CTX was used (single injection of 100 mg kg À1 or less) as a strategy to selectively deplete regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10]27,28 In particular, a number of studies have investigated the combination of CTX with various vaccines. [4][5][6][7]29,30 However, in most of those studies a low dose of CTX was used (single injection of 100 mg kg À1 or less) as a strategy to selectively deplete regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Although this approach may seem counterintuitive as cytotoxic therapies often result in lymphopenia, which could limit the availability of T and B lymphocytes, several recent studies have shown that lymphopenia conditions may actually increase T-cell responsiveness to cancer vaccines. [8][9][10][11] The lymphopenic environment provides more physical space as well as abundance of cytokines and growth factors to promote expansion and differentiation of lymphocytes. In fact, it has been shown that the requirements for T-cell activation under lymphopenic conditions are less stringent and naive T cells can acquire effector-like phenotype and function despite not having been primed through the conventional T-cellantigen-presenting cell interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic benefit of homeostatic proliferation-induced expansion of T cells against tumor antigens was subsequently shown in an animal tumor model (4). We and others have shown that tumor rejection was enhanced by presentation of tumor antigens during homeostatic proliferation in lymphodepleted mice (5)(6)(7)(8). Conversely, homeostatic proliferation was shown to be an obstacle to the induction of transplantation tolerance and a key factor in the development of autoimmune diabetes in nonobese diabetic mice (9,10).…”
Section: Introductionmentioning
confidence: 97%
“…In murine tumor models, induction of lymphopenia followed by adoptive transfer of peptide-specific T cells alone led to regression of established tumors (8). Active vaccination in combination with lymphodepletion and adoptive T cell transfer may further enhance immunity (14,15). Studies have shown that active vaccination can skew the T cell repertoire toward self or tumor-associated antigens during homeostatic proliferation (16,17).…”
Section: Immunotherapy In the Setting Of Nonmyeloablative Lymphodeplementioning
confidence: 99%